Determining factors of individual and organizational unlearning in the generation and realization of ideas: a multigroup analysis from organizational structure - Vanessa Itacaramby Pardim; Luis Hernan Contreras Pinochet; Adriana Backx Noronha Viana; Cesar Alexandre Souza (Innovation & Management Review, 2024)
Purpose This research sought to propose a theoretical model that analyzes the factors associated with unlearning (individual and organizational) and contributes to generating and realizing ideas among young people at the beginning of their careers based on the predominant type of structure. Design/methodology/approach The study had a sample (n = 971) and used the multivariate data analysis partial least squares - Structural Equation Modeling (PLS-SEM regular) and multigroup analysis (PLS-MGA) to identify significant differences between the estimates of the specific parameters of each group (a- Organic/b- Mechanistic). Findings All the direct relationships and formulated mediations were found to be supported, except for H6 (ET→EO) within the group that had a primarily mechanistic organizational structure. Thus, the more turbulent the environmental, the more initiative-taking, innovative and risk-taking a company tends to be. However, it remains to be seen whether the organizational structure plays a role in facilitating or hindering this relationship. H1 (IG→IR) indicates that predominantly organic organizations have a stronger and more consistent relationship with the knowledge developed through individual and organizational unlearning process. This knowledge contributes to the idea-generation process and ultimately leads to realizing those ideas. Originality/value The article contributes to literature by proposing an original and integrated theoretical model incorporating individual and organizational approaches to unlearning to understand the effect on idea generation and realization.
Keywords: 650; Generation of ideas; Individual unlearning; Organizational structure; Organizational unlearning; Realization of ideas